Phenolics production from a novel substrate palm oil mill effluent by aspergillus niger ibs-103za: Evaluation of fermentation conditions and antioxidant activity - Idris, Zulkarnain Mohamed; Jamal, Parveen; Alam, Md Zahangir; Ansari, Abdul Haseeb; Barkat, A. A. (Chiang Mai University, 2015)
This paper introduces palm oil mill effluent (POME) as a novel substrate for production of phenolics under liquid state fermentation by Aspergillus niger IBS-103ZA with selected fermentation conditions. The statistical analysis showed a significant improvement at optimum fermentation conditions of 5.39% (w/v) sucrose, 2.22% (w/v) MnSO4 and a temperature of 35°C. The antioxidant activity of the fermented extract (FE) of POME was evaluated through several in-vitro assays: inhibition of β-carotene bleaching, ferric reducing antioxidant power (FRAP), and inhibition of oxidative hemolysis in human erythrocytes. The results were compared with the synthetic compound, butylated hydroxytoluene (BHT) and the unfermented POME extract (UFE). It was found that the FE has the highest antioxidant activity, based on FRAP assay (FRAP value, 1088.27±34.25 μmol FeSO4.7H2O/g dry extract) and inhibition of oxidative hemolysis (IC50, 0.097±0.020 mg/ml). In case of inhibition of β-carotene bleaching, the FE showed 79.10±5.55% inhibition at a concentration of 0.1 mg/ml.